Pengaruh rasio konsentrasi pada turbin air Savonius - Ida Bagus Alit; Yesung Allo Padang; Mas'ud Mas'ud; Rudy Sutanto; I Gede Bawa Susana (Universitas Mataram, 2020)
Irrigation channels have the potential to be used as power plants. Savonius water turbine can be developed because it has a simple construction and is suitable for low speed, according to the characteristics of the irrigation channel. The objectives of the research were to understand the influence of the installation of concentrator the performance of Savonius water turbine. Concentrator can steer the incoming water flow toward the turbine blades that generate positive moments, consequently, the generated power increases. Variations in the concentration ratios studied were 2: 1, 3: 1, and 4: 1. The results show that adding concentrators can increase torque, turbine power and power coefficient. The best performance of the Savonius water turbine showed is with the concentrator ratio of 3:1.